Microshear bond strength of composite resins to enamel and porcelain substrates utilizing unfilled versus filled resins - Ahmad Najafi-Abrandabadi; Siamak Najafi-Abrandabadi; Amir Ghasemi; Philip G Kotick (Wolters Kluwer Medknow Publications, 2014)
Background: Failures such as marginal discoloration and composite chipping are still the problems of tooth-colored restorations on the substrate of enamel and porcelain, which some of these problems are consequently as a result of failures in the bonding layer. Using filled resin has been recently introduced to increase the bond strength of this layer. The aim of this study was to compare the microshear bond strength (μ-SBS) of composite resins to enamel incubated in periods of 24 h and 9 months and porcelain with unfilled resin and flowable composites (filled resin). Materials and Methods: In this in vitro study, two groups of 75 enamel samples with different storage times (24 h and 9 months) and a group of 75 porcelain samples were used. They were divided into 5 experimental groups of 15 samples in each. Composite cylinders in tygon tubes were bonded on the surface of acid-etched enamel and pretreated porcelain. Wave, Wave MV, Wave HV, Grandioflow and Margin Bond were used as bonding agents. The μ-SBS was measured at the speed of 1.0 mm/min. The bond strengths were analyzed with one-way analysis of variance (ANOVA) test followed by Tukey test. P < 0.05 was selected as the level of statistical significance in this study. Results: The results showed that for enamel (24 h), the μ-SBS of the Wave MV and Wave HV groups were significantly lower than the Margin Bond group. Tukey test indicated the absence of a significant difference between the μ-SBS of the Wave group and the Margin Bond group. However, the μ-SBS of the Grandioflow group was significantly higher than the one for the Margin Bond as a bonding agent. In enamel (9 months), there was a significant difference between the Grandioflow and Margin Bond groups. Regarding bonding to the porcelain the one-way ANOVA test did not show a significant difference among the groups. Conclusion: This study revealed that flowable composites (filled resins) can be used instead of unfilled resins in bonding composite resins to enamel and porcelain substrates.